HUBUNGAN ANTARA KINERJA PETUGAS POSYANDU DENGAN TINGKAT KEPUASAN IBU BALITA (SUATU STUDI DI POSYANDU DESA NGAMPEL KECAMATAN KAPAS KABUPATEN BOJONEGORO) - AINU ZUHRIYAH, AINU ZUHRIYAH; EKO HARI PURNOMO, EKO HARI PURNOMO (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
Integral Health Care (IHC)  is one of the health care program that was already widely known in the community and has been included in the daily social life in rural areas can urban areas. Many opinions from mothers  that they disappointed to  IHC service . The Dissatisfaction is because some services are not provided in IHC. The research objective is to analyze the performance of official relations with the level of satisfaction IHC service.The study design was correlational analytical approach to cross-sectional, population under five mothers who visited the village IHC  Ngampel Bojonegoro Cotton District by 60 respondents, using simple random sampling technique obtained 52 samples of respondents, namely the performance of the independent variables and the dependent variable IHC officers that the level of  Toddler mother satisfaction . data analysis using spearman's rho test.The results of this study the performance of both officers IHC maternal satisfaction with the level of satisfaction as much as 33 respondents (63.5%). While the performance of the  IHC Officer with a sufficient level of maternal satisfaction only eight respondents (15.4%), then amplified by spearman's rho test results are known sig 2-tailed 0.001, and <a (0.05), so H1 is received.In conclusion there is a connection with the performance of officers IHC with  maternal satisfaction rate in IHC toddler Cotton Village District Ngampel Bojonegoro. So it is advisable to IHC officers to provide services in accordance with a system IHC five tables involving midwives, nurses and cadres, as well as explain the procedure prior to the service provided. Keywords: Performance, Satisfaction, Toddler Mother